Biological and economic values of Dipterocarpaceae, the main timber forest product of Indonesia - Wahyu Widiyono (Indonesian Journal of Applied Environmental Studies, 2021)
Dipterocarpaceae is known as a very important tree family both biologically and economically.  Its distribution around the world covers the areas of Peninsular Malaysia, the Philippines, Sumatra, Kalimantan, Java, Sulawesi, Maluku to Papua.  Dipterocarpaceae family has a high economic value, such as producing wood, balsam, resin, charcoal, fat, fruit, bark, essential oil, and camphor. Its products have very important roles for domestic use and export needs. As  representatives of Dipterocarpaceae, the economic value of Shorea Roxb. ex Gaertner f, Dipterocarpus Gaertner f, and Dryobalanops Gaertner f will be discussed. Considering the very important role of Dipterocarpaceae, both biologically and economically, it is necessary to handle it sustainably, through the following actions such as conservation of genetic resources, seed physiology, seed handling, seedling ecology, root symbiosis and nutrition, pest and disease, management of natural forest, and plantation, and also non-timber forest product from Dipterocarpaceae. Dipterocarpaceae dikenal sebagai famili pohon yang sangat penting baik secara biologis maupun ekonomis. Penyebarannya di seluruh dunia meliputi wilayah Semenanjung Malaysia, Filipina, Sumatera, Kalimantan, Jawa, Sulawesi, Maluku hingga Papua. Famili Dipterocarpaceae memiliki nilai ekonomi yang tinggi, seperti menghasilkan kayu, balsam, damar, arang, lemak, buah, kulit kayu, minyak atsiri, dan kapur barus. Produk-produknya memiliki peran yang sangat penting untuk kebutuhan domestik dan ekspor. Sebagai perwakilan Dipterocarpace, nilai ekonomi Shorea Roxb. ex Gaertner f, Dipterocarpus Gaertner f, dan Dryobalanops Gaertner f akan dibahas. Mengingat peranan Dipterocarpaceae yang sangat penting, baik secara biologis maupun ekonomis, maka perlu dilakukan penanganan secara berkelanjutan, melalui tindakan-tindakan seperti konservasi sumber daya genetik, fisiologi benih, penanganan benih, ekologi semai, simbiosis dan nutrisi akar, hama dan penyakit, pengelolaan hutan alam, dan perkebunan, serta hasil hutan bukan kayu dari Dipterocarpaceae.